VOICE IN ACADEMIC WRITING: THE TRANSPOSITIONING OF AUTHOR IDENTITY IN RESPONDING TO MANUSCRIPT BLIND REVIEWERS - Sugiharto, Setiono (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
Voice as one of vital elements in academic writing can impinge upon the quality of one’s writing. Despite robust controversies over the usefulness of this metaphorical notion, a plethora of studies on voice has contributed to our understanding of its role in determining writing quality. The foci of these studies, however, are constricted on either voice as individual or voice as social, ignoring the perspective of voice as dialogic. This case study investigates the written reviews of a manuscript author by four blind reviewers in different international Scopus-indexed journals. Drawing on the ideas of “voice as dialogic” and of “transpositioning” of identity, this study seeks to identify and to examine the authorial strategies of an author in constructing his own voice in textual realizations as responses to the manuscript blind reviewers. In doing so, it attempts to finds out the author’s writing identity as manifested in the texts constructed. Relativism’s methodology was employed in order to provide the construction of certain phenomena (i.e. dialogical voice) as accurately as possible. Results revealed that the manuscript author employed two key authorial strategies: averring established authority and foregrounding the ecologies of knowledges.